Estimated productivity of sugarcane through the Agro-Ecological Zone method - Moura Caetano, Jordana; Alves Júnior, José; Casaroli, Derblai; Pêgo Evangelista, Adão Wagner (Revista Ceres, 2021)
The estimate of the potential sugarcane productivity through agroclimatic models aids in the agricultural planning of the crops and the quantification of the yield for a given region. For these estimated values to be considered robust there is a need for validating the performance of such models in different areas and agricultural varieties. Hence, the aim of this study was to validate the Agro-Ecological Zone (AEZ) method with fifteen sugarcane varieties in the region of the Vale do São Patrício, state of Goiás, Brazil. We evaluated the data referring to the cane-plant (one-and-a-half-year sugarcane), as well as the first and second sugarcane ratoons (both with one-year cycles) in an irrigated and dry farming system. The productivities obtained in dry farming were corrected due to the occurrence of a water deficit in the crop. The results indicated that the AEZ method presented productivity estimates more satisfactory for the one-year cultivation cycles (ratoon cycles) for all varieties studied, with the model adjusting best to the CTC15 variety (RMSE = 8.70 t ha-1; MAE = 6.05 t ha-1; d = 0.99).